Effect of mychorrhizae and rhizobacteria applications on plantlets development of two forest species - Cuervo Andrade, J.L. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),1997